The Fear of SARS-CoV-2 Infection versus the Perception of COVID-19 Vaccination amongst Older Adults in Urban Areas (CoV-VAC-PL Study): A Polish Community-Based Study - Mateusz Cybulski; Andrei Shpakou; Urszula Cwalina (Vaccines, 2024)
Background: The COVID-19 pandemic not only adversely impacted physical health but also affected older adults’ mental health. The first news on COVID-19 vaccination made a major breakthrough to the effect of improving older adults’ mood, notwithstanding the fact that vaccinated individuals in this age group accounted only for 40.6% of the overall vaccination rollout in Poland. This study was aimed at assessing the level of anxiety regarding COVID-19 amongst older adults in Poland and assessing the attitude of older adults toward COVID-19 vaccination. Methods: The study sample encompassed a population of 800 individuals aged 60 years and older randomly picked up from a representative sample of all the residents in 16 voivodeship cities (50 individuals from each of the cities). The research method used in this study was a diagnostic survey, and its technique was based on an author-designed questionnaire and four standardised psychometric scales: the Fear of COVID-19 Scale (FCV-19S), Coronavirus Anxiety Scale (CAS), the Drivers of COVID-19 Vaccination Acceptance Scale (DrVac-COVID-19S), and the Scale to Measure the Perception of SARS-CoV-2 Vaccines Acceptance (the VAC-COVID-19 Scale). Results: The degree of fear of SARS-CoV-2 among seniors equalled 1.03 ± 1.95 in terms of the CAS and 15.61 ± 5.75 in terms of the FCV-19S. Attitudes towards COVID-19 vaccination have proven positive (DrVac-COVID-19S—61.23 ± 12.35; VAC-COVID-19—44.31 ± 7.20). Females scored higher than males to the extent of the scales under consideration. The older the respondents were, the higher the scale score. A group of individuals with higher educational status was characterized by substantially higher scores covering the Knowledge subscale (p < 0.001) and the Autonomy subscale (p = 0.038), as well as a higher total score in terms of the DrVac-COVID-19S (p < 0.001). A group of positive factors including the reasons for COVID-19 vaccination in terms of the VAC-COVID-19 Scale was the only case to prove statistically insignificant relationships between the population size of the city the respondents came from and the scale values under consideration (p = 0.790). Statistically significant relationships were proven between SARS-CoV-2 contraction and fear of COVID-19 as measured by means of the CAS (p < 0.001) as well as between SARS-CoV-2 contraction and the Values subscale (p = 0.017) and the Knowledge subscale (p < 0.001) within the framework of the DrVac-COVID-19S scale and the total score in terms of the DrVac-COVID-19S scale (p = 0.023). No relationship was detected between the Autonomy subscale scores in terms of the DrVac-COVID-19S and the Knowledge subscale scores in terms of the DrVac-COVID-19S. The remaining scales were correlated to the extent of statistical significance. Conclusions: A subjective fear of COVID-19 was measured to be low or moderate within the group under study depending on the scale under consideration, proving declining trends as compared to the results arising from previously conducted studies. Seniors have more often had positive attitudes toward COVID-19 vaccination. The relationship between all of the sociodemographic features under consideration and the feeling of COVID-19 anxiety and between educational status, place of residence, SARS-CoV-2 contraction, COVID-19 vaccination, and the overall attitude toward COVID-19 vaccination indicator was proven to be statistically significant (depending on the scale under consideration). Furthermore, the correlation between the overall results arising from the standardised psychometric scales applied to this study was indicated to be statistically significant.